Designing a reflection learning scale for nurse anesthetist students - Nguyen , Hung Hoa; Ngo , Anh Tuan (Journal of Technical Education Science, 2019)
Reflection is the best competence for students to recognize themselves in learning environment, which helps student apply the tacit knowledge flexibly in a different circumstances. Reflection, therefore, helps learner get effective working by catching tacit knowledge, increase delectation in the cognition and apply their knowledge in different situation in practice. However, the competence of reflection is not easy for evaluating and improving during the learning process, especial in practice. This paper reports the construction and validation of Reflection in Learning Scale (RLS) to estimate the reflection’s ability in Vietnamese Students. The first RLS was mapped a fourteen items scale from literature review and pilot testing of 76 students to find out the construction and validation of RLS. In a series of study three separate factors analyses found the RLS comprised three separate factors, labelled Developing Tacit Knowledge (DTK) with 6 items, Applying for New Situation (ANS) with 3 items and Getting Critical Cognition (GCC) with 3 items. The validations of 3 factors in RLS were 0.83 (DTK), 0.67 (ANS) and 0.76 (GCC). The Likert Scale for RLS was determined with 2 indicators.